Excessive Daytime Sleepiness Is Associated With Non-motor Symptoms of Multiple System Atrophy: A Cross-Sectional Study in China - Wang, Hui; Tang, Xiangdong; Zhou, Junying; Xu, Yanming (Frontiers in Neurology, 2022)
Objectives: Excessive daytime sleepiness (EDS) in multiple system atrophy (MSA) has received scant attention in the literature, thus the present cross-sectional study aimed to investigate the prevalence of EDS and its potential risk factors among Chinese patients with MSA. Methods: A total of 66 patients with MSA (60.6% males) were consecutively recruited. Eighteen patients (27.3%, 13 men) with Epworth Sleepiness Scale score >10 were defined as having EDS. Demographic, motor [Unified Multiple-System Atrophy (UMSARS)] and non-motor symptoms [Non-Motor Symptoms Scale (NMSS)], and sleep parameters [polysomnography (PSG)] were compared between patients with MSA with and without EDS. A logistic regression analysis was used to calculate the risk factors of EDS in patients with MSA. Results: There were no significant differences in age, sex, MSA onset age, disease duration, MSA sub-type, and motor symptom severity between MSA patients with and without EDS. However, compared with the MSA patients without EDS, their counterparts with EDS had higher scores of NMSS (65.3 ± 23.1 vs. 43.4 ± 25.3, P = .0002), Hamilton Anxiety (HAMA) [15.3 (10.3–20.0) vs. 9.5 (3.0–15.0), P = 0.006], Hamilton Depression (HAMD) [13.7 (12.5–17.8) vs. 9.0 (4.0–13.0), P = 0.015], and Fatigue Severity Scale (FSS) [29.8 (17.3–47.8) vs. 18.7 (10.3–21.8), P = 0.040]. Conversely, the patients with EDS had lower score of Mini-Mental State Examination (MMSE) [23.3 (20.3–27.0) vs. 25.7 (22.0–29.0), P = 0.023]. Similarly, there was a significantly lower percentage of N3 sleep (%) [0.3 (0–0) vs. 2.0 (0–0), P = 0.007] and a higher apnea-hypopnea index (AHI/h) [30.5 (14.5–47.8) vs. 19.3 (5.0–28.7), P = 0.034] in patients with EDS. After adjusting for age, sex, disease duration, MSA sub-type, and UMSARS score, the odds ratio (OR) (95% CI) of EDS was higher while increasing scores in FSS [1.06 (1.02–1.11)], HAMA [1.16 (1.04–1.28)], HAMD [1.13 (1.02–1.25)], NMSS [1.04 (1.01–1.07)], and AHI [1.03 (1.00–1.10)]. The OR of EDS was lower while the MMSE score was increasing [0.85 (0.72–1.00)]. Conclusions: The presence and severity of EDS may be significantly associated with the non-motor dysfunction, including fatigue, anxiety, depression, cognitive dysfunction, and sleep-related breathing disorder, but not with the motor dysfunction in MSA.